2006
DOI: 10.1037/0022-0663.98.4.665
|View full text |Cite
|
Sign up to set email alerts
|

Preschool instruction and children's emergent literacy growth.

Abstract: Preschoolers' (N ϭ 156) classroom language and literacy experiences, defined across multiple dimensions, and their vocabulary and emergent literacy development were investigated. Videotaped classroom observations revealed substantial variability in amount and types of language and emergent literacy activities, across classrooms and for individual children within classrooms. Generally, more time in emergent code-focused activities was associated with preschoolers' alphabet and letter-word recognition growth, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
221
3
12

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 353 publications
(252 citation statements)
references
References 85 publications
16
221
3
12
Order By: Relevance
“…It also employs multiple strategies including systematic teacher-directed instruction (National Reading Panel, 2000;Rayner et al, 2001) and child-focused strategies (Snow, 2001), such as peer-assisted tutoring (D. Fuchs & Fuchs, 2005) and reciprocal teaching (Palincsar & Brown, 1984). In this study we use a framework that views instruction multi-dimensionally (Connor et al, in review;Connor, Morrison, & Katch, 2004;Connor, Morrison, & Petrella, 2004;Connor et al, 2006;. Viewing instruction multi-dimensionally, we elucidate the nature and content of instruction, as well as complex child-by-instruction interactions in multiple samples from preschool through third grade.…”
Section: Multiple Dimensions Of Instructionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also employs multiple strategies including systematic teacher-directed instruction (National Reading Panel, 2000;Rayner et al, 2001) and child-focused strategies (Snow, 2001), such as peer-assisted tutoring (D. Fuchs & Fuchs, 2005) and reciprocal teaching (Palincsar & Brown, 1984). In this study we use a framework that views instruction multi-dimensionally (Connor et al, in review;Connor, Morrison, & Katch, 2004;Connor, Morrison, & Petrella, 2004;Connor et al, 2006;. Viewing instruction multi-dimensionally, we elucidate the nature and content of instruction, as well as complex child-by-instruction interactions in multiple samples from preschool through third grade.…”
Section: Multiple Dimensions Of Instructionmentioning
confidence: 99%
“…The extant literature on learning disabilities underscores these findings (Torgesen et al, 2001;Torgesen et al, 1999). Meaning-focused activities-such as reading aloud, teaching comprehension strategies, repeated reading, and vocabulary-predict student outcomes as well (Al'Otaiba et al, in review;Connor, Morrison, & Petrella, 2004;Connor, Morrison, & Slominski, 2006;National Reading Panel, 2000;Snow, 2001).…”
mentioning
confidence: 99%
“…Ha sido revelador el identificar que estas diferencias permanecen estables en su vida escolar (Connor, Morrison y Slominsky, 2006;Muter y Snowling, 2009). Las habilidades de alfabetización que los niños presentan a temprana edad están ligadas al desarrollo del lenguaje oral y escrito, como es el vocabulario (Mol, Bus, Jong y Smeets, 2008), la conciencia fonológica (Bus, van Ijzendoorn y Pellegrini, 1995), la identificación de letras (Martini y Sénéchal, 2012), así como el conocimiento y manejo de diferentes conceptos de texto impreso (Mol y Bus, 2011).…”
Section: Introductionunclassified
“…When it comes to teachers' self-reported educational goals, it has been suggested that a high extent of enriching literacy activities can provide a high quality classroom environment supporting children's academic development. For example, Connor, Morrison and Slominski (2006) found that the amount and type of language and literacy activities observed in classrooms consisting of four-year-olds had a significant and systematic relation to the children's growth in their knowledge of the alphabet, letterword recognition and vocabulary skills.…”
Section: The Importance Of Teachers' Self-reported Educational Goalsmentioning
confidence: 99%